Perilaku Pemeliharaan Kesehatan Gigi dan Mulut pada Anak Autisme - Ervon Veriza; Hendry Boy (Universitas Faletehan, 2018)
Children with special needs is one of Indonesia's human resources whose quality must be improved in order to play a role, not only as the object of development but also as the subject of development. Children with special needs need to be identified and identified from the group of children in general, because they require special services, such as medical services, special education and specific exercises aimed at reducing the limitations and dependence of the disorder suffered, and foster self-reliance in the community. The purpose of this study was to obtain in-depth information about dental and oral health care behavior in children with autism in Harapan Mulia Special School in South Jambi. Qualitative research method using indepth interview with triangulation of source that is parent or caregiver, teachers and psychologist who build in SLB Harapan Mulia. The results show that the behavior of maintaining good oral hygiene in children with autism depending on the mother or caregiver. Supporting factors include the availability of dental and oral health facilities are still lacking, most of the informants looking for dental services or dentists who are known or trusted, not crowded so that children can also be comfortable and children not too long waiting. Reinforcing factor the behavior of maintaining good oral hygiene in children with autism at home is his mother or caregiver, while in school is a teacher companion.